Pengaruh Work-Life Balance dan Kepuasan Kerja terhadap Retensi Karyawan : Studi pada Karyawan PT. Nakau Lampung Utara - Astrid Monika; Akhir Lusono; Diana Anggraini Kusumawati (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
This study aims to examine the effect of Work-Life Balance and Job Satisfaction on Employee Retention at PT. Nakau, North Lampung. Employee retention is a crucial issue in human resource management because it directly relates to the sustainability and effectiveness of an organization. This study uses a quantitative approach with data obtained through distributing questionnaires to 93 respondents who are company employees. The analysis method used is multiple linear regression to determine the simultaneous and partial effects of the independent variables on the dependent variable. The results show that Work-Life Balance has a positive and significant effect on Employee Retention, as well as Job Satisfaction which has been proven to have a positive contribution in increasing retention. Simultaneously, these two variables play an important role in encouraging employees to remain in the company. These findings have an implicit impact on enriching the human resource management literature, particularly regarding retention strategies based on work-life balance and job satisfaction. In addition, practically, this study provides recommendations to companies to design policies and programs that support work-life balance and create a satisfying work environment, thereby increasing loyalty and reducing employee turnover rates.